Geochemical and grain size data of core Co1309, Lake Ladoga, Russia - Raphael Gromig; Bernd Wagner; Volker Wennrich; Grigory B Fedorov; Larisa Savelieva; Elodie Lebas; Sebastian Krastel; Dominik Brill; Andrei A Andreev; Dmitry A Subetto; Martin Melles (PANGAEA, 2021)
Lake Ladoga in northwestern Russia is Europe extquotesingles largest lake. The postglacial history of the Ladoga basin is for the first time documented continuously with high temporal resolution in the upper 13.3 m of a sediment core (Co1309) from the northwestern part of the lake. We applied a multiproxy approach including (bio-)geochemical and granulometric analyses. The dataset comprises grain-size data (clay, silt, sand), biogeochemical data (total organic carbon (TOC), total sulphur (TS)), water content and XFR data (Fe, P, Ti, K, Zr, Ti/Al, Rb/Sr, Zr/Rb) of the composit profile of sediment core Co1309 as presented in Gromig et al. 2019.